Effects Of Performance Measurement System And The Role Of Clarity Performance Manajer (Studies In Banking Manager) - siti khoirina; Novalita Novalita (Jurnal Akuntansi Malikussaleh (JAM), 2023)
This study aimed to investigate the effects of performance measurement system on the performance of  managers. This research was conducted in the banking sector, in Lampung, Palembang, Jambi and Bengkulu. Of the 113 people who responded to the questionnaire, we analyzed the data using Stuctural Equation Modeling test equipment (SEM), smart PLS and test track, and we found that a comprehensive performance measurement makes it possible to improve the performance of managers directly. However, the clarity of the role of the majority gives a better aspect to improve the performance of managers and some will not. This study revealed that the clarity of the role of the services sector, especially the banking sector makes it possible to motivate managers to work better.